Energy Storage: Nitrogen‐Doped Ordered Mesoporous Anatase TiO2 Nanofibers as Anode Materials for High Performance Sodium‐Ion Batteries (Small 26/2016). Issue 26 (7th July 2016) - Wu, Ying; Liu, Xiaowu; Yang, Zhenzhong; Gu, Lin; Yu, Yan
Abstract : On page 3522, Y. Yu and co‐workers fabricate nitrogen‐doped ordered mesoporous TiO2 nanofibers (denoted as N‐MTO) by electrospinning and subsequent nitridation treatment. Nitrogen atoms are successfully doped into the TiO2 lattice, accompanied by the formation of Ti 3+ and oxygen vacancies, contributing to the improvement of electronic conductivity of TiO2 . When used as an anode for a sodium‐ion battery, the N‐MTO demonstrates excellent rate capability and superior long cycling performance.